THE EFFECTIVENESS OF QRIS PAYMENTS IN AN ISLAMIC PERSPECTIVE BASED ON PADG NO.24/1/PADG/2022 - Afiatur Rahimah; Pitri Yani (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2023)
Kendari city is a religious city, this is marked by the many mosques built in every corner of the city, one of the mosques that has become an iconic place for the people of Kendari city is the al-alam mosque which was built in 2010 which features beautiful views, the al- Alam is located in the middle of the Kendari Bay sea so that it gives a different feel from other mosques in the city of Kendari, the Al-Alam Mosque is a religious tourism destination that is often visited by both local and foreign tourists. The payment system cannot be separated from the development of money, which started from cash payments to non-cash payments. Many development agencies facilitate transactions that are effective in making payments, one of which is QRIS, which is an electronic money payment application such as an electronic wallet, server based. or mobile banking that is used by users for digital money payments is different. QRIS aims to offer a lot of comfort and convenience for its users with a variety of features that are useful and have advantages that are not in doubt the safety and effectiveness of the QRIS payment system for its users.